Tahap Preliminary Research Pengembangan LKPD Berbasis PBL Materi Peluang Kejadian Majemuk - Jamila Wati; Zulfah (Jurnal Inovasi Matematika, 2020)
The purpose of this research is to conduct an initial analysis in developing students' worksheets (Lembar Kerja Peserta Didik, LKPD) based on Problem Based Learning (PBL) to develop mathematical problem-solving ability optimally. This research used the first stage on the ADDIE Model, an analysis model. Analysis activity in this research was begun with need analysis, learners’ analysis, curriculum analysis, and construct analysis. Based on the result of the analysis stage, it can be concluded that to be able to strengthen students’ ability to fix mathematical problems, teachers provide learning resources that will facilitate students to enhance and develop their mathematical problem-solving abilities on multiple occurrence opportunities material. Through the students’ worksheet which is based on PBL as a proven approach, the use of students’ worksheets can help learners develop their problem-solving ability.